2022
DOI: 10.3122/jabfm.2022.04.210529
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot of a Randomized Control Trial of Melatonin and Vitamin C for Mild-to-Moderate COVID-19

Abstract: This study aimed to help determine the effect of dietary supplements on symptom course and quality of life in patients with mild-to-moderate COVID-19 infection.Design: We modified the Wisconsin Upper Respiratory Symptom Survey (WURSS) to conduct a 3 arm, parallel, randomized, double-blind, placebo-controlled trial, enrolling patients with mild-to-moderate symptoms of COVID-19 infection. Patients took placebo (n = 34), vitamin C 1000 mg (n = 32), or melatonin 10 mg (n = 32) orally for 14 days.Outcomes: Ninety E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…Anderson et al demonstrated melatonin could improve some COVID-19 symptoms consistent with our obtained results (Anderson and Reiter 2020 ). Randomized controlled trial conducted in Lancaster County, Pennsylvania, United states had shown oral melatonin could improve clinical symptoms in mild–moderate COVID-19 patient during 14 days of intervention and improve life quality (Fogleman et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Anderson et al demonstrated melatonin could improve some COVID-19 symptoms consistent with our obtained results (Anderson and Reiter 2020 ). Randomized controlled trial conducted in Lancaster County, Pennsylvania, United states had shown oral melatonin could improve clinical symptoms in mild–moderate COVID-19 patient during 14 days of intervention and improve life quality (Fogleman et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…A total of 140 records were screened during the electronic database searching process, and two additional studies were retrieved by screening reference lists of related articles. Eventually, nine RCTs involving 718 subjects were identified and included in the final meta-analyses (13)(14)(15)(27)(28)(29)(30)(31)(32). In the experimental group, the intervention consisted of melatonin plus standard care, while in the control group, nearly all comparators were standard care alone (15,(27)(28)(29)(30)(31)(32), except for two studies that included a matched placebo (13,14) (Supplementary Table 2).…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…However, these findings were based on small numbers of randomized controlled trials (RCTs). Recently, more RCTs with larger sample sizes have been published, but with opposing results and findings (13)(14)(15). To resolve this conflicting issue, we conducted this Abbreviations: CIs, confidence intervals; COVID-19, coronavirus pandemic disease 2019; CRP, C-reactive protein; ESR, erythrocyte sedimentation rate; ICU, intensive care units; ITT, intention-to-treat; MDs, mean differences; NLR, neutrophil to lymphocyte ratio; PP, per-protocol; PRISMA, preferred reporting items for systematic review and meta-analysis; RCTs, randomized controlled trials; RoB, risk-of-bias; RR, relative risk; TSA, trial sequential analysis; SARS-CoV-2, severe acute respiratory syndrome coronavirus 2.…”
Section: Introductionmentioning
confidence: 99%
“…In a pilot study conducted on the quality of life of patients in the US with mild to moderate COVID-19 severity, 32 patients who were supplemented with 10 mg of melatonin daily for 14 days had a more rapid improvement in their quality of life than the placebo group of 34 patients [ 166 ]. In a randomized single-blind pilot study of Iranian patients with mild to moderate COVID-19 severity, 14 patients received 6 mg of melatonin for 2 weeks.…”
Section: Melatonin and Covid-19mentioning
confidence: 99%